Acute Thyroiditis in a Patient with Neck Trauma - Peralta, Pearl Marian A.; Yu, Jeryl Ritzi T.; Hernandez, Edrome F.; dela Fuente, Evangeline B. (Case Reports in Psychiatry, 2022)
The management of patients with major depressive disorder who present with self-injurious behavior is best optimized through a collaborative interprofessional approach. We describe a case of a 27-year-old woman without personal or family history of thyroid pathology who presented at the emergency department due to a suicide attempt by hanging. On examination, she was tachycardic with palpitations which persisted despite administration of analgesics and anxiolytics. Left temporal area swelling, left otorrhagia, and neck contusion were noted, involving consults with the Trauma, Neurosurgery, and Otorhinolaryngology teams. She was admitted to the psychiatric ward on account of persistent suicidal ideations. As part of the workup, thyroid function tests were done to rule out hypothyroidism as a cause of depressive symptoms. Results instead showed suppressed thyroid stimulating hormone and elevated free T4. Endocrinology service was consulted, and further workup showed absence of avid uptake of both thyroid glands on thyroid scan and undetectable thyrotropin receptor antibody level, supportive of a diagnosis of trauma-induced thyroiditis. This case increases awareness that trauma-induced thyroid dysfunction should be considered in patients with symptoms including, but not limited to, tachycardia and palpitations after a traumatic neck injury such as hanging.